PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACION DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE BEBIDA ENERGIZANTE A BASE DE GUAYUSA EN LA CIUDAD DE LOJA - Coronel Loaiza, Richard Mauricio (2016)
This research was conducted in the city of Loja, aiming to present a proposal to implement a producer and marketer of an energy drink Guayusa based company. Among the objectives to be raised it is to conduct market research to meet current demand, supply and unsatisfied demand, perform technical study to determine the macro and micro location, presenting a functional organic- company proposal to be implemented, and finally make a financial study to establish investment and financing of the project and to determine the feasibility or otherwise of the project under study. With regard to the methods used it took into account the scientific method to reach pose the problem, the deductive method to review the theoretical framework, the inductive method to complete the project's profitability and the descriptive method to describe the facts and social events. The market study is framed in a descriptive research method. The technique of data collection was through a survey. The information obtained from the application of the instrument was processed through a qualitative approach using proprietary descriptive and supported by the theoretical basis of study techniques. In the technical study the macro and micro location of the company indicates, the installed capacity and used detailed, labor is needed for production. As for the administrative organization, has raised a limited liability company, is disclosed hierarchical levels and manuals, flow charts to define the company handle activities and tasks that staff must make every day. EcoDrinks CIA. LTDA ~ 5 ~ Finally the project evaluation was performed to establish the suitability of the project and its implementation for which the following indicators as the Financial Evaluation was analyzed, this project has the following indicators: Net Present Value of $ 42.719,80 Internal Rate of Return to 122,58%; Relationship Benefit Cost is $ 1.66 for every dollar invested company earns 0.66 cents; Capital Recovery Period is 10 months and 2 days; Sensitivity analysis indicates that the project supports an increase in costs of 41% for a total of 0.99% and the sensitivity analysis in the decrease in revenues of 24% giving a total of 0.89%, so the project is feasible, the conclusions and recommendations so determined, accompanied by the bibliography consulted with their respective annexes.